2022
DOI: 10.1109/tcds.2019.2958423
|View full text |Cite
|
Sign up to set email alerts
|

Effective Brain Connectivity for fNIRS With Fuzzy Cognitive Maps in Neuroergonomics

Abstract: Effective connectivity (EC) amongst functional near-infrared spectroscopy (fNIRS) signals is a quantitative measure of the strength of influence between brain activity associated with different regions of the brain. Evidently, accurate deciphering of EC gives further insight into the understanding of the intricately complex nature of neuronal interactions in the human brain. This work presents a novel approach to estimate EC in the human brain signals using enhanced fuzzy cognitive maps (FCMs). The proposed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…For six out of a total of seven classifiers, the H0 1 is rejected hence establishing that it is possible to recognise gamer's expertise level from fNIRS neural responses from the PFC with recognition performance better than a 95% confidence interval difference to the results from a baseline classifier. This is inline with previous studies which found professional on-line gamers to have an increased brain volume in the PFC [25], and from the literature we know that subjects at different 475 expertise levels have different patterns of activation in their PFC [28,31].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For six out of a total of seven classifiers, the H0 1 is rejected hence establishing that it is possible to recognise gamer's expertise level from fNIRS neural responses from the PFC with recognition performance better than a 95% confidence interval difference to the results from a baseline classifier. This is inline with previous studies which found professional on-line gamers to have an increased brain volume in the PFC [25], and from the literature we know that subjects at different 475 expertise levels have different patterns of activation in their PFC [28,31].…”
Section: Discussionsupporting
confidence: 91%
“…In this work, fNIRS is used to image participant’s brain activity owing to the superior spatial resolution and resistance to motion artifacts in comparison to EEG [ 30 ]. In addition, previous fNIRS studies from our group have aimed to gauge technical skill levels assessment for surgeons with varying levels of experience in the study by Andreu-Perez et al [ 28 ] and Kiani et al [ 31 ]. In Andreu-Perez et al [ 28 ] the surgeons perform a complex bi manual coordination task whilst their brain activity is recorded using fNIRS.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…An fNIRS study that estimated EC amongst fNIRS channels (corresponding anatomical regions in the cortex) based on fuzzy cognitive maps (FCMs) is proposed by Kiani et al [58]. A FCM is a cognitive mapping technique based on graph theory, with a formal mathematical definition given as follows in (1).…”
Section: A) Ec With Fnirs Using Effective Fuzzy Cognitive Maps (Efcms)mentioning
confidence: 99%
“…where N is the number of concepts (or fNIRS channels) in a given system, C j (t) is the value of a given concept C j at iteration t, e ij are the fuzzy weights or EC that concept C i exerts on concept C j and f is typically a sigmoid function that scales the weights to [-1,1] for comparative analysis such that a value of 1 means fully interconnected, a value of -1 means fully interconnected in the opposite direction, a value of 0 means disconnected, and a value between 0 and 1 (or -1) means interconnected to a certain extent. The optimal values of EC (e ij ) are typically found using an evolutionary algorithm such as Genetic algorithm (GA) (GA has also been used in the aforementioned study [58]).…”
Section: A) Ec With Fnirs Using Effective Fuzzy Cognitive Maps (Efcms)mentioning
confidence: 99%